An Ayurvedic Approach to Vrikka Rog: Case Study of Chronic Kidney Disease Management in a Pediatric Patient - Manish, Acharya; Richa; Rao, Ashish; Rani, Tanu; Chandrasekharan, Prabha (International Research Journal of Ayurveda & Yoga, 2026)
Chronic Kidney Disease (CKD), described in Ayurveda as Vrikk Rog and Mutravah Srotas Vyadhi, is attributed to the vitiation of Vata and Kapha doshas, along with the disturbance of Rakta and Medadhatus. This case study presents a 12-year-old male diagnosed with CKD, managed at the Jeena Sikho Lifecare Limited Clinic in Bhagalpur through a personalised Ayurvedic regimen. Treatment included specific Ayurvedic formulations, dietary modifications, and dosha–balancing interventions targeting Apana Vata and urinary obstructions. The patient demonstrated progressive clinical improvement, with notable relief in symptoms such as shoth (oedema), Mutravikara (urinary difficulty), Klama (fatigue), and respiratory discomfort. Laboratory findings corroborated clinical recovery, including a significant reduction in serum creatinine. Ayurvedic management, focusing on detoxification, metabolic correction, and rejuvenation, was found effective in improving both subjective well-being and objective health markers. This case supports the potential role of integrative Ayurvedic approaches in the supportive management of pediatric CKD.